Insecticide-Treated Bed Nets Ownership, Utilization and Potency on Anopheles population from Gombe, North East, Nigeria - Abdulmalik B.S.; Sow, G.J; Chiezey, N; Yoriyo, K. P; Abba, E; Ubayo, A; Ndams, I.S., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
Malaria vector control relies principally on the use of chemical-based control strategies of LLINs and IRS at the community level. This study aimed at evaluating insecticide-treated bed-nets ownership, utilization and potency against Anopheles populations from Akko and Kaltungo LGA Gombe State, Nigeria. The study was carry-out in eight (8) communities between January and December, 2022. A well-structured questionnaire containing 24 items was administered in each of the communities for insecticide-treated bed-net ownership and utilization and two bed-nets were sampled to determine potency. The immature Anopheles were collected from breeding sites using the standard dipper in eight communities and reared to adulthood in the laboratory. All the tests were conducted at the temperature of 25˚-33˚ C and relative humidity of 60-80%. The bio-assayed females were identified morphologically using dichotomous key of Coetzee. The results showed high bed-net ownership (98.9%) and ITNs utilization (93.8%) among the respondents’ household. Despite the high rate of bed-nets ownership the level of utilization is still below 100% recommendation of WHO. Moreover, DuraNet (98%), Olyset-plus (100%) PermaNet 3.0(98%) showed optimal effectiveness while Netprotect (3%) with minimal effectiveness. In conclusion, high bed net ownership and utilization among residential households was established with efficacy on Anopheles after long term usage. Therefore, more awareness campaign is recommended in the study area to achieve maximum control and elimination of malaria vectors.